9th International Drainage Symposium Held Jointly With CIGR and CSBE/SCGAB Proceedings, 13-16 June 2010, Québec City Convention 2010
DOI: 10.13031/2013.32146
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Removal of Drainage Water with Barley Straw as a Bioreactor Filter

Abstract: Nitrate is a widespread groundwater contaminant, which can cause pollution of receiving waters. Some of the highest losses of nitrate to surface waters come from drained agricultural land. Bioreactor filters are a useful approach for removing nitrate from drainage waters, but these systems require an external carbon supply to sustain denitrification. The ability of barley straw to serve as a carbon substrate for biofilters was evaluated in a laboratory model. In this study the effect of two heads (100 and 200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Lastly, much research has been conducted in laboratory settings as it represents a step prior to pilot or full-scale trials (Tikhomirova et al, 2018). Hashemi et al (2010) showed a NO 3 -N reduction rate of 60% to 70% for laboratory bioreactors filled with barley straw. Similarly, Kouanda and Hua (2021) reported nitrate reductions of 15% for barley straw and 11% for wood in the laboratory, while Hellman et al (2021) reported NO 3 -N reductions of 42% for barley and 44% for wood in their laboratory study.…”
Section: Evaluation Of Different Carbon Sources For No3-n Removalmentioning
confidence: 99%
“…Lastly, much research has been conducted in laboratory settings as it represents a step prior to pilot or full-scale trials (Tikhomirova et al, 2018). Hashemi et al (2010) showed a NO 3 -N reduction rate of 60% to 70% for laboratory bioreactors filled with barley straw. Similarly, Kouanda and Hua (2021) reported nitrate reductions of 15% for barley straw and 11% for wood in the laboratory, while Hellman et al (2021) reported NO 3 -N reductions of 42% for barley and 44% for wood in their laboratory study.…”
Section: Evaluation Of Different Carbon Sources For No3-n Removalmentioning
confidence: 99%